Residual insomnia in major depressive disorder: a systematic review - Kwaśny, Aleksander; Włodarczyk, Adam; Dywel, Alicja; Szarmach, Joanna; Strandberg, Olivia; Cubała, Wiesław Jerzy (Frontiers in Psychiatry, 2023)
The ultimate goal in major depressive disorder (MDD) treatment is recovery. A proportion of MDD patients with formal remission experience persistent difficulties, which impair their daily functioning. Residual insomnia is one of the most common residual symptoms. Patients with residual insomnia experience relapse significantly earlier and have a poor prognosis. Little is known about possible ways of treatment and what subtype of insomnia is mostly reported. Methods: A systematic literature review was carried out in PubMed and Web of Science to synthesize the current status of knowledge about effective treatment methods and insomnia subtypes in residual insomnia in MDD. Results: A few non-pharmacological treatment methods e.g. Cognitive Behavioral Therapy for Insomnia (CBT-I), Mindfulness-Based Cognitive Therapy (MBCT), behavioral activation (BA) and pharmacological methods (gabapentin, clonazepam) have proven to mitigate residual insomnia. Cognitive Behavioral Therapy for Depression (CBT-D) ameliorates insomnia complaints to a limited extent. Mid-nocturnal insomnia is the most common residual insomnia subtype in MDD patients. Conclusion: Residual insomnia is a very common complaint and most often appears as mid-nocturnal insomnia. Scarce data points out the benefits from pharmacotherapy, psychotherapy, and BA. More research is needed.